In an equilateral triangle ABC, D is a point on the side BC such that \[BD = \dfrac{1}{3}BC\], then show that $9A{D^2} = 7A{B^2}$.
Answer
Verified
483.3k+ views
Hint: First, we will form the triangle according to given conditions, then draw an altitude in it to use pythagorean theorem such that it contains the sides BD and BC so that we can use the given condition \[BD = \dfrac{1}{3}BC\] and thus find the result.
Complete step-by-step answer:
Let us draw the figure first as shown below:
Here, ABC is the given triangle and \[BD = \dfrac{1}{3}BC\]. Let P be a point on BC such that AP is the altitude and we have drawn AD as well because we need the condition $9A{D^2} = 7A{B^2}$ which contains AD.
Consider the $\vartriangle APC$ and $\vartriangle APB$:
$AB = AC$ (Since the triangle is equilateral)
$AP = AP$ (Common)
$\angle B = \angle C$ (Both are ${60^ \circ }$ because of being angles in equilateral triangle)
Hence, $\vartriangle APC \cong \vartriangle APB$ (By SAS property)
SAS property states that two triangles are congruent if they have a pair of equal corresponding angles and two pairs of corresponding equal sides.
Hence, we have $BP = PC$ (By C.P.C.T) …..(1)
$BP + PC = BC = AB$
Using (1), we have:
$BP = PC = \dfrac{1}{2}BC = \dfrac{1}{2}AB$ ……(2)
CPCT stands for Corresponding parts of Congruent triangles. CPCT theorem states that if two or more triangles which are congruent to each other are taken then the corresponding angles and the sides of the triangles are also congruent to each other.
Let us now first get to know the pythagorean theorem:
It says that if we have a right angled triangle, right angled at B, then $A{C^2} = A{B^2} + B{C^2}$
Now consider the $\vartriangle ABP$:-
Applying pythagorean theorem on it, we get:
$A{B^2} = A{P^2} + P{B^2}$
This implies that $A{P^2} = A{B^2} - P{B^2}$
Using (2), we will get:-
$\therefore A{P^2} = A{B^2} - {\left( {\dfrac{1}{2}AB} \right)^2}$
$\therefore A{P^2} = A{B^2} - \dfrac{1}{4}A{B^2}$
$\therefore A{P^2} = \dfrac{{4A{B^2} - A{B^2}}}{4} = \dfrac{{3A{B^2}}}{4}$ …….(3)
Now, consider $\vartriangle ADP$:-
Applying pythagorean theorem on it, we get:
$A{D^2} = A{P^2} + P{D^2}$ ……(4)
Applying (3) in (4), we get:-
$A{D^2} = \dfrac{3}{4}A{B^2} + D{P^2}$ …..(5)
We clearly see that $BD + DP = BP$
So, we have: $DP = BP - BD$
Putting this in (5), we will get:-
$A{D^2} = \dfrac{3}{4}A{B^2} + {(BP - BD)^2}$ …….(6)
We are given that \[BD = \dfrac{1}{3}BC\] and since ABC is an equilateral triangle which means $AB = BC$.
This implies \[BD = \dfrac{1}{3}BC = \dfrac{1}{3}AB\] …….(7)
Using (1) and (7) in (6), we get:
$A{D^2} = \dfrac{3}{4}A{B^2} + {(\dfrac{1}{2}AB - \dfrac{1}{3}AB)^2}$
Simplifying RHS:
$A{D^2} = \dfrac{3}{4}A{B^2} + \dfrac{1}{{36}}A{B^2}$
Simplifying the RHS further:
$A{D^2} = \dfrac{3}{4}A{B^2} + \dfrac{1}{{36}}A{B^2} = \dfrac{{27 + 1}}{{36}}A{B^2} = \dfrac{{28}}{{36}}A{B^2}$
Cross multiplying:
$36A{D^2} = 28A{B^2}$
Cutting 4 from both sides:
$9A{D^2} = 7A{B^2}$
Hence, we have proved the required expression.
Note: The students may make the mistake of applying the pythagorean theorem on the triangles ABD and ACD but, you must always remember that, we need a right angled triangle to apply the pythagorean theorem.
Complete step-by-step answer:
Let us draw the figure first as shown below:
Here, ABC is the given triangle and \[BD = \dfrac{1}{3}BC\]. Let P be a point on BC such that AP is the altitude and we have drawn AD as well because we need the condition $9A{D^2} = 7A{B^2}$ which contains AD.
Consider the $\vartriangle APC$ and $\vartriangle APB$:
$AB = AC$ (Since the triangle is equilateral)
$AP = AP$ (Common)
$\angle B = \angle C$ (Both are ${60^ \circ }$ because of being angles in equilateral triangle)
Hence, $\vartriangle APC \cong \vartriangle APB$ (By SAS property)
SAS property states that two triangles are congruent if they have a pair of equal corresponding angles and two pairs of corresponding equal sides.
Hence, we have $BP = PC$ (By C.P.C.T) …..(1)
$BP + PC = BC = AB$
Using (1), we have:
$BP = PC = \dfrac{1}{2}BC = \dfrac{1}{2}AB$ ……(2)
CPCT stands for Corresponding parts of Congruent triangles. CPCT theorem states that if two or more triangles which are congruent to each other are taken then the corresponding angles and the sides of the triangles are also congruent to each other.
Let us now first get to know the pythagorean theorem:
It says that if we have a right angled triangle, right angled at B, then $A{C^2} = A{B^2} + B{C^2}$
Now consider the $\vartriangle ABP$:-
Applying pythagorean theorem on it, we get:
$A{B^2} = A{P^2} + P{B^2}$
This implies that $A{P^2} = A{B^2} - P{B^2}$
Using (2), we will get:-
$\therefore A{P^2} = A{B^2} - {\left( {\dfrac{1}{2}AB} \right)^2}$
$\therefore A{P^2} = A{B^2} - \dfrac{1}{4}A{B^2}$
$\therefore A{P^2} = \dfrac{{4A{B^2} - A{B^2}}}{4} = \dfrac{{3A{B^2}}}{4}$ …….(3)
Now, consider $\vartriangle ADP$:-
Applying pythagorean theorem on it, we get:
$A{D^2} = A{P^2} + P{D^2}$ ……(4)
Applying (3) in (4), we get:-
$A{D^2} = \dfrac{3}{4}A{B^2} + D{P^2}$ …..(5)
We clearly see that $BD + DP = BP$
So, we have: $DP = BP - BD$
Putting this in (5), we will get:-
$A{D^2} = \dfrac{3}{4}A{B^2} + {(BP - BD)^2}$ …….(6)
We are given that \[BD = \dfrac{1}{3}BC\] and since ABC is an equilateral triangle which means $AB = BC$.
This implies \[BD = \dfrac{1}{3}BC = \dfrac{1}{3}AB\] …….(7)
Using (1) and (7) in (6), we get:
$A{D^2} = \dfrac{3}{4}A{B^2} + {(\dfrac{1}{2}AB - \dfrac{1}{3}AB)^2}$
Simplifying RHS:
$A{D^2} = \dfrac{3}{4}A{B^2} + \dfrac{1}{{36}}A{B^2}$
Simplifying the RHS further:
$A{D^2} = \dfrac{3}{4}A{B^2} + \dfrac{1}{{36}}A{B^2} = \dfrac{{27 + 1}}{{36}}A{B^2} = \dfrac{{28}}{{36}}A{B^2}$
Cross multiplying:
$36A{D^2} = 28A{B^2}$
Cutting 4 from both sides:
$9A{D^2} = 7A{B^2}$
Hence, we have proved the required expression.
Note: The students may make the mistake of applying the pythagorean theorem on the triangles ABD and ACD but, you must always remember that, we need a right angled triangle to apply the pythagorean theorem.
Recently Updated Pages
Express the following as a fraction and simplify a class 7 maths CBSE
The length and width of a rectangle are in ratio of class 7 maths CBSE
The ratio of the income to the expenditure of a family class 7 maths CBSE
How do you write 025 million in scientific notatio class 7 maths CBSE
How do you convert 295 meters per second to kilometers class 7 maths CBSE
Write the following in Roman numerals 25819 class 7 maths CBSE
Trending doubts
Full Form of IASDMIPSIFSIRSPOLICE class 7 social science CBSE
The Island of Bombay was given to the English Prince class 7 social science CBSE
Convert 200 Million dollars in rupees class 7 maths CBSE
Fill in the blanks with appropriate modals a Drivers class 7 english CBSE
What are the controls affecting the climate of Ind class 7 social science CBSE
The southernmost point of the Indian mainland is known class 7 social studies CBSE